Antioxidant copper powder and preparation method thereof

By forming a protective film of silane and polyaniline layer on the surface of copper particles, the problem of degradation of conductive properties caused by oxidation of copper powder is solved, and excellent anti-oxidation and conductive properties are achieved, which broadens the application range of copper powder.

CN119282104APending Publication Date: 2025-01-10FOSHAN LONGXIN NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411415190.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Copper powder causes air oxidation to deteriorate its conductivity, and the existing antioxidant measures are not effective, which affects its application, especially in the field of electronic pastes.

Method used

After forming a thin silane layer on the surface of the copper particles, a polyaniline organic layer is covered with a layer to form a uniform and dense organic protective film to improve oxidation resistance and maintain conductive properties.

Benefits of technology

It significantly reduces the oxidation rate of copper particles, improves the oxidation resistance and high temperature resistance, and maintains low resistivity, making it suitable for applications in many fields such as electronic pastes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005079990630000121
    Figure BDA0005079990630000121
  • Figure BDA0005079990630000131
    Figure BDA0005079990630000131
  • Figure BDA0005079990630000132
    Figure BDA0005079990630000132
Patent Text Reader

Abstract

The invention provides antioxidant copper powder and a preparation method thereof. The antioxidant copper powder sequentially comprises copper particles, a silane layer and a polyaniline layer from inside to outside, the D50 of the antioxidant copper powder is 1.5 to 3.5 [mu] m; the mass ratio of the silane layer in the antioxidant copper powder is 0.05-0.1%; and the mass ratio of the polyaniline layer in the antioxidant copper powder is 0.1-0.5%. A layer of uniform and compact organic matter protective film is arranged on the surface of the antioxidant copper powder, so that the contact between internal copper particles and external air is effectively reduced, and the probability that the copper particles are oxidized is greatly reduced. Meanwhile, the organic protective films on the surfaces of the copper particles have better temperature resistance and conductivity, so that the influence on the conductivity of the copper particles is smaller, and the obtained antioxidant copper powder has lower resistivity. The antioxidant copper powder provided by the invention has excellent oxidation resistance and conductivity at the same time, is copper powder with excellent performance, is suitable for being applied to various fields, especially the field of electronic paste, and widens the application range and application scene of the copper powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal powder processing, and particularly relates to an anti-oxidation copper powder and a preparation method thereof. Background Art

[0002] Metallic copper plays a very important role in modern industry and modern life due to its excellent thermal and electrical conductivity, soft texture, wear resistance, corrosion resistance, non-magnetic, antibacterial and beautiful color, and easy alloying with other materials. It is widely used in various industrial fields such as electrical, light industry, machinery manufacturing, chemistry, construction, and national defense.

[0003] Copper powder is a functional basic powder material with high-tech content and high added value, and is also one of the fastest-growing hot products in the field of materials. In addition to the good electrical conductivity, thermal conductivity, corrosion resistance, smooth surface and non-magnetic properties of metallic copper, copper powder, as a functional powder material, is widely used in powder metallurgy, friction materials, oil-containing bearings, electrical contact materials, conductive materials, diamond products and mechanical parts, as well as emerging petroleum catalysts, lubricants, conductive and decorative coatings and electromagnetic shielding materials.

[0004] Although copper powder has many excellent properties as mentioned above, it has the defect that it is easily oxidized by air, which affects its own conductive properties to a certain extent. At present, there are relatively many means to slow down the oxidation of copper powder, most of which are to coat a layer of organic coating agent or antioxidant on its surface (organic coating agent is: stearic acid, sodium stearate, and oleic acid, etc.; antioxidant is: ascorbic acid, phosphoric acid and its salts, metaphosphoric acid and its salts, etc.) to slow down the probability of copper powder being oxidized. The effect of this method in inhibiting the oxidation of copper powder is not very ideal. For better antioxidant properties, the amount of coating agent must be increased, but the increase in the amount of coating agent seriously affects the conductive properties of copper powder.

[0005] In view of this, providing a copper powder that can simultaneously take into account antioxidant properties and conductive properties is of great significance for the practical application of copper powder. Summary of the invention

[0006] In order to solve the problems and shortcomings in the prior art, the present invention provides an antioxidant copper powder and a preparation method thereof. The surface of the antioxidant copper powder is provided with a uniform and dense organic protective film, which effectively reduces the contact between the internal copper particles and the external air, and greatly reduces the probability of the copper particles being oxidized. At the same time, since the organic protective film on the surface of the copper particles has good temperature resistance and conductivity, it has little effect on the conductivity of the copper particles, and the obtained antioxidant copper powder has a lower resistivity. That is, the antioxidant copper powder provided by the present invention can take into account its excellent antioxidant performance and conductive performance at the same time, and is a copper powder with excellent performance, which is suitable for application in various fields, especially in the field of electronic slurries, and broadens the application range and application scenarios of copper powder.

[0007] According to a first aspect of the present invention, an antioxidant copper powder is provided, which comprises copper particles, a silane layer, and a polyaniline layer from the inside to the outside; the D50 of the antioxidant copper powder is 1.5 to 3.5 μm; the mass proportion of the silane layer in the antioxidant copper powder is 0.05 to 0.1%; the mass proportion of the polyaniline layer in the antioxidant copper powder is 0.1 to 0.5%.

[0008] The antioxidant copper powder provided by the present invention has copper particles at the innermost part. The copper particles themselves have low antioxidant properties. In order to improve the antioxidant properties of copper particles, the prior art usually directly coats a layer of antioxidant on the surface of the copper particles. However, copper particles are metal particles, and the properties of ordinary antioxidants are quite different from those of metal copper particles. On the one hand, the coating effect will be relatively poor, that is, the antioxidant effect will be poor. On the other hand, usually such antioxidants need to be coated thicker to improve the antioxidant properties, but this will affect the electrical conductivity of copper itself, thereby limiting the application of copper.

[0009] First, the present invention forms a thin silane layer on the surface of the copper particles through a special design, and then forms a thinner polyaniline organic layer on the basis of the silane layer, which greatly improves the coating effect of the anti-oxidation film layer on the surface of the copper particles, such as the polyaniline organic layer, and effectively improves the anti-oxidation performance of the copper particles. Specifically, the surface of the copper particles will have certain hydroxyl groups on the surface due to contact with air or some treatments, and silanes such as silane coupling agents will have hydrolysis groups, and the two can react, so the silane coupling agent can be well grafted on the surface of the copper particles. In this way, when the polyaniline organic layer continues to be formed on this basis, the silane layer formed by the silane coupling agent generally has some organic active groups, and these organic active groups can react with the polyaniline organic matter to form chemical bonds, so the polyaniline organic matter can be well attached to the surface of the silane layer to form a uniform and dense organic film. Polyaniline and its derivatives have strong antioxidant and high temperature resistance, and can resist the attack of oxidants. Therefore, when the polyaniline organic matter is tightly and evenly coated on the outer surface of the copper particles through the silane layer, the antioxidant and high temperature resistance of the copper particles are effectively improved, and the surface of the copper particles can be kept from being corroded for a long time, which greatly improves the stability of the copper particles. At the same time, when the silane layer is first formed on the surface of the copper particles, the silane coupling agents in the silane layer can crosslink and condense with each other through the silanol group to form a preliminary network structure film on the surface of the copper particles, which can prevent the oxidation of the copper particles to a certain extent. Therefore, under the joint action of the silane layer and the polyaniline organic matter layer, the surface of the copper particles is less likely to expose the original surface, that is, it is less likely to be oxidized and corroded, thereby further improving the antioxidant performance of the copper particles.

[0010] In addition, polyaniline is a polymer compound with special electrical and optical properties, especially excellent electrical conductivity and electrochemical properties. The electrical activity of polyaniline comes from the P electron conjugated structure in the molecular chain. When polyaniline is activated by electrons, the number of electrons does not change, but the proton acid decomposes to produce H + The anions enter the main chain and combine with the N atoms in the amine and imine groups to form polar and dipole delocalization to the P bonds of the entire molecular chain, so that polyaniline exhibits higher conductivity and excellent electrochemical properties. Therefore, this makes the copper particles coated with polyaniline have lower resistivity and has less impact on the original conductive properties of the copper particles, which effectively ensures the excellent conductive properties of the copper particles themselves.

[0011] Secondly, in the antioxidant copper powder provided by the present invention, the mass proportion of the silane layer and the polyaniline organic layer in the antioxidant copper powder is only 0.05-0.1% and 0.1-0.5%, respectively, which means that the silane layer and the polyaniline organic layer are very thin, which means that in the present invention, since the silane layer plays a bridging role between the copper particles and the polyaniline organic layer, the antioxidant effect of the polyaniline organic layer on the copper particles is effectively improved, and the silane layer itself also has a certain antioxidant effect, so that the copper particle surface is only coated with a thinner silane layer and a polyaniline layer to achieve a better antioxidant effect on the copper particles. At the same time, the thinner silane layer and the polyaniline layer have little effect on the conductive properties of the copper particles themselves, and the polyaniline itself has excellent conductive properties, which can further promote the antioxidant copper powder to have better conductive properties.

[0012] Third, the particle size of the anti-oxidation copper powder in the present invention is within the above-mentioned specific range, which is more conducive to taking into account its electrical conductivity and anti-oxidation performance as well as comprehensive performance in many aspects. The particle size of the copper powder will directly affect the conductive effect. When the particle size of the copper powder is too large, its specific surface area and surface energy will be reduced accordingly, which will deteriorate the electrical conductivity and thermal conductivity of the copper powder. Therefore, the particle size of the copper powder should not be too large. However, if the particle size of the copper powder is too small, the finer copper powder is more susceptible to oxidation. Even if a certain anti-oxidation film is coated, it is still more susceptible to external conditions due to the smaller particle size of the copper powder, and is more susceptible to oxidation. The coating effect of the anti-oxidation film on the copper particles will be poor. And the anti-oxidation copper powder that is too fine indicates that the particle size of the copper particles is also smaller at the beginning, which will cause the difficulty of coating outside it to become greater. Therefore, even if it is coated, the anti-oxidation effect after coating is not as expected. Therefore, the appropriate copper powder particle size is the key to ensuring the conductive effect and the anti-oxidation effect.

[0013] When copper powder is usually used as electronic paste, particles with too small a size may lead to poor fluidity, which is not conducive to uniform distribution and coating. Particles with too large a size may cause difficulties in screen printing, because larger particles are not easy to pass through the screen, which will affect the quality and efficiency of printing. In addition, particles with too large a size may also affect the uniformity and stability of the paste, thereby affecting the performance of the final product.

[0014] Preferably, the D50 of the antioxidant copper powder is 1.5 to 2.5 μm. Further controlling the D50 of the antioxidant copper powder within the above range is more conducive to taking into account both the antioxidant performance and the conductive performance of the copper powder. At the same time, it is also more conducive to the further use of the antioxidant copper powder, such as the application in electronic paste. Within the above D50 range, it is more conducive to the dispersion stability and subsequent processability of the electronic paste prepared therefrom.

[0015] Preferably, the D50 of the copper particles is 1.4 to 2.5 μm. Controlling the D50 of the copper particles within the above range is conducive to reducing the difficulty of coating, so that the coating effect of the silane layer and the polyaniline layer formed on the surface is better, and the final anti-oxidation copper powder has a more suitable D50, which is more conducive to taking into account its anti-oxidation performance, conductive performance, and subsequent processing and use performance.

[0016] Preferably, the copper particles include at least one of spherical copper particles, quasi-spherical copper particles, and flaky copper particles. These types of copper particles can form a relatively uniform and dense polyaniline organic layer on their surface, which can significantly improve the antioxidant properties of these types of copper particles without affecting their conductive properties.

[0017] Preferably, the silane layer includes at least one of aminopropyltriethoxysilane, glycidoxypropyltrimethoxysilane, methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, and triethoxymethylsilane.

[0018] Preferably, the silane layer includes glycidoxypropyl trimethoxysilane; or, the silane layer includes glycidoxypropyl trimethoxysilane and vinyl trimethoxysilane. Glycidoxypropyl trimethoxysilane is a bifunctional organosilane with three methoxy groups on one side and an epoxy ring on the other side, so it has a high reactivity in water. Therefore, compared with other silane coupling agents, it exhibits better bridging performance when used as a connector between metal particles such as copper particles and polymers such as polyaniline, and is more conducive to more uniform and dense coating of organic substances such as polyaniline on the surface of copper particles. However, the use of a certain amount of silane coupling agent will also affect the conductivity of copper particles to some extent, and the use of glycidoxypropyl trimethoxysilane and vinyl trimethoxysilane is more conducive to taking into account the conductivity and antioxidant properties of copper particles. This is because vinyl trimethoxysilane contains vinyl groups and can form a large conjugated structure with polyaniline, which is conducive to electron transmission, so its use is more conducive to the overall conductivity of copper particles. Therefore, by using glycidyloxypropyltrimethoxysilane and vinyltrimethoxysilane, the obtained antioxidant copper powder can better balance the antioxidant performance and the conductive performance, which is more conducive to improving the comprehensive performance of the antioxidant copper powder.

[0019] Preferably, the silane layer includes glycidyloxypropyl trimethoxysilane and vinyl trimethoxysilane, and the mass ratio of glycidyloxypropyl trimethoxysilane to vinyl trimethoxysilane is 1 to 3: 1. Under the above mass ratio, the combination of the two has a better effect, which is more conducive to the antioxidant performance and conductive performance of the antioxidant copper powder.

[0020] According to a second aspect of the present invention, there is provided a method for preparing the above-mentioned antioxidant copper powder, comprising the following steps: S1. copper particles, organic solvent A, water and silane coupling agent are placed in a reactor and mixed to obtain a first mixed system; S2. the pH of the first mixed system is adjusted to 3-6, and then the mixture is placed at 40-60°C for constant temperature reaction for 1-5 hours. After the reaction is completed, the obtained solid is washed and dried to obtain pretreated copper particles; S3. the pretreated copper particles are mixed with water, and then aniline monomer is added thereto and continued to mix, and then an initiator solution is added, and the mixture is reacted at room temperature for 30-60 minutes, and the obtained solid is washed and dried to obtain antioxidant copper powder. Under the reaction conditions of the above steps, such as the reaction conditions in S2, the silane coupling agent can be well hydrolyzed in water and grafted on the surface of the copper particles, and a silane layer is initially formed on the surface of the copper particles. Further, under the reaction conditions of S3, especially the reaction conditions at room temperature, aniline can form a polyaniline coating layer with high crystallinity, good crystallinity, good conductivity and dense and uniformity on the silane layer, so that the finally obtained antioxidant copper powder has higher antioxidant and conductive properties.

[0021] Preferably, in S1, the mass ratio of copper particles to silane coupling agent is 5-20:0.1-0.5.

[0022] Preferably, in S1, the copper particles are treated with acid. The surface of the acid-treated copper particles has more hydroxyl groups and higher surface activity, so the silane coupling agent has a better grafting effect on them and can form a more stable silane layer, thereby further promoting the formation of a uniform and dense film of polyaniline on the silane layer.

[0023] Preferably, the copper particles are treated with dilute sulfuric acid.

[0024] Preferably, in S1, the organic solvent A comprises ethanol; and the mass ratio of the organic solvent to water is 100:2-8.

[0025] Preferably, in S1, the mass concentration of the copper particles in the first mixed system is 5-20%; the mass concentration of the silane coupling agent in the first mixed system is 0.1-0.5%.

[0026] Preferably, in S1, after copper particles, organic solvent A, water and silane coupling agent are placed in a reactor and mixed, ultrasonic dispersion is further performed for 0.5 to 2 hours. Ultrasonic dispersion for a certain period of time can promote the hydrolysis of the silane coupling agent and the dispersion of the copper particles, thereby promoting the grafting of the silane coupling agent on the surface of the copper particles, improving the grafting stability of the silane coupling agent on the surface of the copper particles, and further improving the uniformity, density and stability of the polyaniline coating.

[0027] Preferably, in S2, the pH of the first mixed system is adjusted to 3-6 by using an acid; the acid comprises acetic acid.

[0028] Preferably, in S2, the mass ratio of the pretreated copper particles to the aniline monomer is 5 to 20:0.5 to 1. By controlling the mass ratio of the pretreated copper particles to the aniline monomer within the above range, the polyaniline layer formed by the aniline monomer on the surface of the pretreated copper particles can be controlled to be neither too thin nor too thick, which is conducive to taking into account both the antioxidant performance and the conductive performance of the copper powder finally obtained.

[0029] Preferably, in S2, the mass ratio of the pretreated copper particles, the aniline monomer and the initiator is 5-20:0.5-1:1-5; the initiator comprises at least one of tert-butyl peroxide, hydrogen peroxide, benzoyl peroxide and ammonium persulfate.

[0030] Preferably, the initiator comprises ammonium persulfate.

[0031] Preferably, in S2, the initiator solution is added dropwise, and mixing is performed while adding dropwise. Adding the initiator solution dropwise can control the speed of initiating the polymerization of the aniline monomer, which is conducive to forming a uniform and dense polyaniline film on the surface of the pretreated copper particles, thereby promoting the improvement of its antioxidant performance and conductive performance.

[0032] Preferably, the mass concentration of the initiator solution is 5-15%. DETAILED DESCRIPTION

[0033] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only embodiments of a part of the present invention, rather than all embodiments.

[0034] Example 1

[0035] The antioxidant copper powder of this embodiment is prepared according to the following steps:

[0036] S1. 8 g of spherical copper particles (D50 of 2 μm, treated with dilute sulfuric acid), 100 g of anhydrous ethanol, 5 g of deionized water and 0.4 g of a silane coupling agent, glycidyloxypropyltrimethoxysilane, were added to a beaker and ultrasonically dispersed for 1 h to form a first mixed system;

[0037] S2. Add acetic acid to the first mixed system to adjust the pH to about 4, then transfer to a flask and react at 50°C for 2h; after the reaction, cool and filter, wash twice with anhydrous ethanol, and dry in vacuo at 60°C to obtain pretreated copper powder;

[0038] S3. Put 8g of pretreated copper powder sample and 80g of deionized water into a three-necked flask and stir it with a magnetic force to make a suspension; add 0.5g of aniline monomer to the suspension, stir for 30min, and then slowly add 15g of 10% ammonium persulfate solution while stirring; after the addition is completed, react at room temperature for 50min, filter out the solid product, wash it 3 times with deionized water and dry it to obtain antioxidant copper powder.

[0039] After relevant tests such as testing with a particle size analyzer, the D50 of the obtained antioxidant copper powder is 2.03μm, and testing using methods such as thermogravimetric testing shows that the mass proportion of the silane layer in the antioxidant copper powder is 0.08%, and the mass proportion of the polyaniline layer in the antioxidant copper powder is 0.37%.

[0040] Example 2

[0041] The antioxidant copper powder of this embodiment is prepared according to the following steps:

[0042] S1. 13 g of spherical copper particles (D50 of 2 μm, treated with dilute sulfuric acid), 100 g of anhydrous ethanol, 5 g of deionized water and 0.8 g of a silane coupling agent, glycidyloxypropyltrimethoxysilane, were added to a beaker and ultrasonically dispersed for 1 h to form a first mixed system;

[0043] S2. Add acetic acid to the first mixed system to adjust the pH to about 4, then transfer to a flask and react at 50°C for 2h; after the reaction, cool and filter, wash twice with anhydrous ethanol, and dry in vacuo at 60°C to obtain pretreated copper powder;

[0044] S3. Put 13g of pretreated copper powder sample and 80g of deionized water into a three-necked flask and stir it with a magnetic force to make a suspension; add 0.8g of aniline monomer to the suspension, stir for 30 minutes, and then slowly add 25g of 10% ammonium persulfate solution while stirring; after the addition is completed, react at room temperature for 50 minutes, filter out the solid product, wash it with deionized water 3 times, and then dry it to obtain antioxidant copper powder.

[0045] After relevant tests such as testing with a particle size analyzer, the D50 of the obtained antioxidant copper powder is 2.04μm, and testing using methods such as thermogravimetric testing shows that the mass proportion of the silane layer in the antioxidant copper powder is 0.09%, and the mass proportion of the polyaniline layer in the antioxidant copper powder is 0.41%.

[0046] Example 3

[0047] In the process of preparing the antioxidant copper powder of this embodiment, the difference from that of embodiment 1 is that the D50 of the quasi-spherical copper particles used in S1 is 2.47 μm (after being treated with dilute sulfuric acid). The rest of the operations are the same as those of embodiment 1.

[0048] After relevant tests such as testing with a particle size analyzer, the D50 of the obtained antioxidant copper powder is 2.5μm, and testing using methods such as thermogravimetric testing shows that the mass proportion of the silane layer in the antioxidant copper powder is 0.08%, and the mass proportion of the polyaniline layer in the antioxidant copper powder is 0.39%.

[0049] Example 4

[0050] The process of preparing the antioxidant copper powder of this embodiment is different from that of Example 1 in that the D50 of the quasi-spherical copper particles used in S1 is 3.46 μm (after being treated with dilute sulfuric acid). The rest of the operations are the same as those of Example 1.

[0051] After relevant tests such as testing with a particle size analyzer, the D50 of the obtained antioxidant copper powder is 3.5μm, and testing using methods such as thermogravimetric testing shows that the mass proportion of the silane layer in the antioxidant copper powder is 0.09%, and the mass proportion of the polyaniline layer in the antioxidant copper powder is 0.42%.

[0052] Example 5

[0053] The process of preparing the antioxidant copper powder of this embodiment is different from that of embodiment 1 in that the silane coupling agent used in S1 is vinyltrimethoxysilane. The rest of the operations are the same as those of embodiment 1.

[0054] After relevant tests such as testing with a particle size analyzer, the D50 of the obtained antioxidant copper powder is 2.04μm, and testing using methods such as thermogravimetric testing shows that the mass proportion of the silane layer in the antioxidant copper powder is 0.08%, and the mass proportion of the polyaniline layer in the antioxidant copper powder is 0.36%.

[0055] Example 6

[0056] In the process of preparing the antioxidant copper powder of this embodiment, the difference from that of Example 1 is that the silane coupling agent used in S1 is methacryloxypropyltrimethoxysilane+vinyltrimethoxysilane, and the mass ratio of methacryloxypropyltrimethoxysilane to vinyltrimethoxysilane is 2:1. The rest of the operations are the same as those of Example 1.

[0057] After relevant tests such as testing with a particle size analyzer, the D50 of the obtained antioxidant copper powder is 2.06μm, and testing using methods such as thermogravimetric testing shows that the mass proportion of the silane layer in the antioxidant copper powder is 0.08%, and the mass proportion of the polyaniline layer in the antioxidant copper powder is 0.39%.

[0058] Example 7

[0059] In the process of preparing the antioxidant copper powder of this embodiment, the difference from that of Example 1 is that the silane coupling agent used in S1 is glycidyloxypropyl trimethoxysilane + vinyl trimethoxysilane, and the mass ratio of glycidyloxypropyl trimethoxysilane to vinyl trimethoxysilane is 2:1. The rest of the operations are the same as those of Example 1.

[0060] After relevant tests such as testing with a particle size analyzer, the D50 of the obtained antioxidant copper powder is 2.04μm, and testing using methods such as thermogravimetric testing shows that the mass proportion of the silane layer in the antioxidant copper powder is 0.08%, and the mass proportion of the polyaniline layer in the antioxidant copper powder is 0.45%.

[0061] Example 8

[0062] In the process of preparing the antioxidant copper powder of this embodiment, the difference from that of Example 1 is that the silane coupling agent used in S1 is glycidyloxypropyl trimethoxysilane + vinyl trimethoxysilane, and the mass ratio of glycidyloxypropyl trimethoxysilane to vinyl trimethoxysilane is 4:1. The rest of the operations are the same as those of Example 1.

[0063] After relevant tests such as testing with a particle size analyzer, the D50 of the obtained antioxidant copper powder is 2.05μm, and testing using methods such as thermogravimetric testing shows that the mass proportion of the silane layer in the antioxidant copper powder is 0.08%, and the mass proportion of the polyaniline layer in the antioxidant copper powder is 0.43%.

[0064] Example 9

[0065] In the process of preparing the antioxidant copper powder of this embodiment, the difference from that of embodiment 1 is that the copper particles used in S1 are flaky copper particles. The rest of the operations are the same as those of embodiment 1.

[0066] After relevant tests such as testing with a particle size analyzer, the D50 of the obtained antioxidant copper powder is 2.04μm, and testing using methods such as thermogravimetric testing shows that the mass proportion of the silane layer in the antioxidant copper powder is 0.07%, and the mass proportion of the polyaniline layer in the antioxidant copper powder is 0.38%.

[0067] Comparative Example 1

[0068] The process of preparing the antioxidant copper powder of this comparative example is different from that of Example 1 in that step S3 is not performed, that is, the polyaniline layer is not coated, and the copper powder pretreated in S2 is used as the antioxidant copper powder of this comparative example. The rest of the operations are the same as those of Example 1.

[0069] Comparative Example 2

[0070] In the process of preparing the antioxidant copper powder of this comparative example, the difference from Example 1 is that step S2 is not performed, that is, the copper particles are not treated with a silane coupling agent and are directly coated with a polyaniline layer, wherein the operation of S1 is consistent with that of Example 1, and the specific operation of S3 is as follows: 0.5 g of aniline monomer is added to the first mixed system, and after stirring for 30 minutes, 15 g of a 10% ammonium persulfate solution is slowly added dropwise while stirring; after the addition is completed, the reaction is carried out at room temperature for 50 minutes, the solid product is filtered out, washed three times with deionized water, and then dried to obtain the antioxidant copper powder.

[0071] Comparative Example 3

[0072] The antioxidant copper powder of this comparative example was prepared according to the following steps:

[0073] 10 g of quasi-spherical copper powder (D50 is 2 μm, treated with dilute sulfuric acid) and 5 g of deionized water were put into a beaker, 0.5 g of 10% oleic acid ethanol solution was added, stirred and dispersed for 20 minutes, filtered and dried to obtain antioxidant copper powder.

[0074] Comparative Example 4

[0075] The antioxidant copper powder of this comparative example was prepared according to the following steps:

[0076] 10 g of spherical copper powder (D50 is 2 μm, treated with dilute sulfuric acid) and 5 g of deionized water were put into a beaker, 0.5 g of 10% benzotriazole ethanol solution was added, stirred and dispersed for 20 minutes, filtered and dried to obtain antioxidant copper powder.

[0077] Comparative Example 5

[0078] The spherical copper powder without surface treatment (D50 of 2 μm, treated with dilute sulfuric acid) was directly used as the object of subsequent related performance tests.

[0079] Comparative Example 6

[0080] In the process of preparing the antioxidant copper powder of this comparative example, the difference from Example 1 is that the silane coupling agent in S1 is adjusted to 0.2 g. The rest of the operations are the same as those in Example 1.

[0081] After relevant tests such as testing with a particle size analyzer, the D50 of the obtained antioxidant copper powder is 2.01μm, and testing using methods such as thermogravimetric testing shows that the mass proportion of the silane layer in the antioxidant copper powder is 0.03%, and the mass proportion of the polyaniline layer in the antioxidant copper powder is 0.25%.

[0082] Comparative Example 7

[0083] In the process of preparing the antioxidant copper powder of this comparative example, the difference from Example 1 is that the silane coupling agent in S1 is adjusted to 1.2 g. The rest of the operations are the same as those in Example 1.

[0084] After relevant tests such as testing with a particle size analyzer, the D50 of the obtained antioxidant copper powder is 2.07μm, and testing using methods such as thermogravimetric testing shows that the mass proportion of the silane layer in the antioxidant copper powder is 0.18%, and the mass proportion of the polyaniline layer in the antioxidant copper powder is 0.39%.

[0085] Comparative Example 8

[0086] In the process of preparing the antioxidant copper powder of this comparative example, the difference from Example 1 is that the aniline monomer in S3 is adjusted to 1.2 g. The rest of the operations are the same as in Example 1.

[0087] After relevant tests such as testing with a particle size analyzer, the D50 of the obtained antioxidant copper powder is 2.09μm, and testing using methods such as thermogravimetric testing shows that the mass proportion of the silane layer in the antioxidant copper powder is 0.08%, and the mass proportion of the polyaniline layer in the antioxidant copper powder is 0.7%.

[0088] Comparative Example 9

[0089] The process of preparing the antioxidant copper powder of this embodiment is different from that of embodiment 1 in that the D50 of the quasi-spherical copper particles used in S1 is 3.86 μm (after being treated with dilute sulfuric acid). The rest of the operations are the same as those of embodiment 1.

[0090] After relevant tests such as testing with a particle size analyzer, the D50 of the obtained antioxidant copper powder is 3.9μm, and testing using methods such as thermogravimetric testing shows that the mass proportion of the silane layer in the antioxidant copper powder is 0.13%, and the mass proportion of the polyaniline layer in the antioxidant copper powder is 0.55%.

[0091] Comparative Example 10

[0092] In the process of preparing the antioxidant copper powder of this embodiment, the difference from that of embodiment 1 is that the D50 of the quasi-spherical copper particles used in S1 is 0.98 μm (after being treated with dilute sulfuric acid). The rest of the operations are the same as those of embodiment 1.

[0093] After relevant tests such as testing with a particle size analyzer, the D50 of the obtained antioxidant copper powder is 1 μm, and testing using methods such as thermogravimetric testing shows that the mass proportion of the silane layer in the antioxidant copper powder is 0.04%, and the mass proportion of the polyaniline layer in the antioxidant copper powder is 0.09%.

[0094] Test Case

[0095] 1. Experimental Construction Method

[0096] The antioxidant copper powder or untreated copper powder prepared in all the above embodiments and comparative examples was tested for its antioxidant properties and resistivity properties. The specific testing methods are as follows:

[0097] (1) The antioxidant performance test was conducted using a thermogravimetric analyzer under the following test conditions: in an air atmosphere and at a heating rate of 1°C / min (without dwelling at the corresponding temperature conditions), a thermogravimetric analysis was performed on the antioxidant copper powders prepared in all the above embodiments and comparative examples or untreated copper powder (50 mg), and the degree of oxidation on the surface of the copper powder in air was determined and measured by the trend of mass increase.

[0098] (2) The resistivity performance test uses a powder resistance meter with a pressure of 10 MPa and a cross-sectional area of ​​78.5 mm 2 , the resistivity of copper powder after heat treatment at a certain temperature is calculated according to the formula, ρ = (R·S) / L;

[0099] Where: ρ is resistivity (mΩ·cm); R is resistance (mΩ), S is area (78.5mm 2 ), L is the length (mm).

[0100] 2. Experimental results

[0101] The test results of the antioxidant properties and resistivity properties of the antioxidant copper powder or untreated copper powder prepared in all the above embodiments and comparative examples are shown in Tables 1 and 2, respectively.

[0102] Table 1 Summary of antioxidant performance data of antioxidant copper powder or untreated copper powder

[0103]

[0104]

[0105] Table 2 Summary of resistivity performance data of antioxidant copper powder or untreated copper powder

[0106]

[0107] From the analysis of the relevant performance data in Tables 1 and 2 above, it can be seen that the weight change rate of the antioxidant copper powder provided by the present invention at high temperature is low, and the resistivity at high temperature is also low, specifically refer to Examples 1 to 9. Therefore, the antioxidant copper powder provided by the present invention has excellent antioxidant performance and conductive performance.

[0108] Comparative Examples 1, 2, 3 and 4 are all coated with a single layer of material. The silane layer in Comparative Example 1 has general antioxidant properties, which also leads to poor conductivity of the antioxidant copper powder at a high temperature of 150°C. The polyaniline layer in Comparative Example 2 has poor adhesion to the copper particles and is difficult to coat or unevenly coated, resulting in poor antioxidant properties. At the same time, it also leads to poor conductivity of the antioxidant copper powder at a high temperature of 150°C. In Comparative Examples 3 and 4, oleic acid and benzotriazole are used as copper particle coating agents, respectively, which have certain antioxidant properties at 200°C. The copper powder in Comparative Examples 3 and 4 has poor conductivity at a high temperature of 150°C, and the weight gain at 300°C is more than 15%. Comparative Example 5 is a copper particle without coating treatment, which is easily oxidized at room temperature. The weight gain at 300°C is more than 25%, and without any coating, the conductivity of the copper particles at a high temperature of 150°C is the worst. The coated silane layer in Comparative Example 6 is relatively thin, which will affect the subsequent coating effect of polyaniline, resulting in relatively low antioxidant performance. The coating layer of Comparative Examples 7 and 8 is too thick, which is better in antioxidant effect, but the coating layer is too thick, which will have a certain impact on the conductivity of the antioxidant copper powder, so the conductivity of the antioxidant copper powder decreases at a high temperature of 150°C. The antioxidant copper powder D50 in Comparative Examples 9 and 10 is too large and too small, respectively. Both too large and too small are not conducive to taking into account both its conductive properties and antioxidant properties. If it is too large, the coating layer may be thicker, affecting the conductivity. If it is too small, it is more easily oxidized, affecting the antioxidant properties. After excessive oxidation, the conductivity will also be affected.

[0109] Further comparing Example 1 and Example 2, it is found that the only difference between Example 1 and Example 2 is the material ratio, and the final antioxidant properties are equivalent.

[0110] Comparing Example 1, Example 3, and Example 4, although the D50 of the antioxidant copper powder in Example 4 is larger, that is, the coating accounts for a larger proportion, and its antioxidant performance is better, the coating thickness is large, which will affect its conductive performance. Therefore, the high-temperature conductivity in Example 4 is relatively poor.

[0111] Comparing Example 1, Example 5, Example 6, Example 7 and Example 8, it is to use different coupling agents for coating. After comparison, it can be seen that the combination of two coupling agents is better than a single one. And through further data comparison, in Example 7, the coating is carried out using the scheme of glycidyloxypropyltrimethoxysilane + vinyltrimethoxysilane 2:1, and the obtained antioxidant copper powder has the best antioxidant property and the best conductivity. This shows that the type selection or matching of silane coupling agents will also have a certain influence on the antioxidant performance and conductivity of the antioxidant copper powder, and the appropriate type matching is more conducive to further optimizing the antioxidant performance and conductivity of the antioxidant copper powder.

[0112] Comparing Example 1 and Example 9, Example 9 uses flaky copper particles for coating, and the effect is equivalent to that of Example 1. The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are within the protection scope of the present invention.

Claims

1. An antioxidant copper powder, characterized in that: The anti-oxidation copper powder comprises copper particles, a silane layer, and a polyaniline layer in sequence from the inside to the outside; The D50 of the antioxidant copper powder is 1.5 to 3.5 μm; The mass proportion of the silane layer in the anti-oxidation copper powder is 0.05-0.1%; The mass proportion of the polyaniline layer in the anti-oxidation copper powder is 0.1-0.5%.

2. The anti-oxidation copper powder according to claim 1, characterized in that: The D50 of the anti-oxidation copper powder is 1.5-2.5 μm.

3. The anti-oxidation copper powder according to claim 1, characterized in that: The copper particles include at least one of spherical copper particles, quasi-spherical copper particles, and flaky copper particles.

4. The anti-oxidation copper powder according to claim 1, characterized in that: The silane layer includes at least one of aminopropyl triethoxysilane, glycidoxypropyl trimethoxysilane, methacryloxypropyl trimethoxysilane, vinyl trimethoxysilane, and triethoxymethylsilane.

5. The antioxidant copper powder according to claim 4, characterized in that: The silane layer includes the glycidyloxypropyltrimethoxysilane; Alternatively, the silane layer includes the glycidyloxypropyltrimethoxysilane and the vinyltrimethoxysilane.

6. The antioxidant copper powder according to claim 5, characterized in that: The silane layer includes the glycidyloxypropyltrimethoxysilane and the vinyltrimethoxysilane, and the mass ratio of the glycidyloxypropyltrimethoxysilane to the vinyltrimethoxysilane is 1 to 3:

1.

7. The method for preparing the antioxidant copper powder according to any one of claims 1 to 6, characterized in that: The steps include: S1. The copper particles, the organic solvent A, water and the silane coupling agent are placed in a reactor and mixed to obtain a first mixed system; S2. Adjust the pH of the first mixed system to 3 to 6, and then place it at a constant temperature of 40 to 60 ° C for 1 to 5 hours. After the reaction is completed, wash and dry the obtained solid to obtain pretreated copper particles; S3. Mix the pretreated copper particles with water, then add aniline monomer thereto and continue mixing, then add initiator solution, react at room temperature for 30 to 60 minutes, wash and dry the obtained solid to obtain the antioxidant copper powder.

8. The method for preparing the antioxidant copper powder according to claim 7, characterized in that: In S1, the mass ratio of the copper particles to the silane coupling agent is 5-20:0.1-0.

5.

9. The method for preparing the antioxidant copper powder according to claim 7, characterized in that: In the S1, the copper particles are treated with acid.

10. The method for preparing the antioxidant copper powder according to claim 7, characterized in that: In S2, the mass ratio of the pretreated copper particles to the aniline monomer is 5-20:0.5-1.